Multi-decade northward shift of loggerhead sea turtle pelagic habitat as the eastern North Pacific Transition Zone becomes more oligotrophic - Dana K. Briscoe; Larry B. Crowder; George H. Balazs; Jeffrey A. Seminoff; Alberto Abreu; Catherine A. Lee Hing; Masanori Kurita; Masanori Mori; Denise M. Parker; Marc R. Rice; Tomomi Saito; Bianca S. Santos; et al. (Frontiers in Marine Science, 2025)
The North Pacific Transition Zone (NPTZ) is known as a global marine hotspot for many endangered and commercially significant highly mobile marine species. In the last few decades, the region has undergone unprecedented physical and biological transformations in response to climate variability and change. Although it is anticipated that many highly mobile species will need to adapt and shift their distributions, current predictions have relied on short-term data sets or modeled simulations. This has left a critical gap in our understanding of long-term (decadal or longer) change and species’ responses within the NPTZ. Here, we integrate nearly 3 decades of satellite tracking data from a climate sentinel, the juvenile North Pacific loggerhead sea turtle ( Caretta caretta ), with concurrent observations of sea surface temperature (SST) and chlorophyll-a concentrations to examine higher trophic level response to climate-induced changes within the eastern bounds of the NPTZ. Between 1997–2024, the NPTZ has warmed by 1.6°C and experienced an approximately 19% decline in mean surface chlorophyll-a concentration, a proxy for reduced productivity, resulting in a 28% (1.65 million km 2 ) increase in total oligotrophic habitat in the eastern NPTZ. Over the same period, the average latitude of loggerhead sea turtle foraging habitat in the NPTZ has shifted northwards by 450–600 km. This represents a distributional shift rate of 116–200km/decade. In most years both the southern and northern range limits for the loggerhead turtle have shifted northward in tandem, indicating a habitat range shift rather than a range expansion. Our findings reveal significant physical and biological change to the NPTZ over the last quarter century and the first empirical evidence illustrating the substantial spatial response of a highly mobile megafaunal species. As the NPTZ continues to become more oligotrophic, these insights can provide vital information for dynamic conservation and management strategies within this critically important ecosystem.